Research on ship motion characteristics in a cross sea based on computational fluid dynamics and potential flow theory. Issue 1 (31st December 2023) - Lu, Yu; Shao, Wu; Gu, Zhuhao; Wu, Chunxiao; Li, Chuang
ABSTRACT: The motion response of a ship in a cross sea is studied based on computational fluid dynamics. Firstly, according to the established numerical pool, and based on the Reynolds-averaged Navier–Stokes equations and the re-normalisation group K – ϵ turbulence model, the free surface is treated by the volume of fluid(VOF) method, and a numerical simulation method is established. The wave results obtained by the numerical simulation are compared with theoretical waves to verify the reliability of the method. Then, considering the DTMB5415 ship model, a prediction method for the ship's motion in a cross sea is established by using an overlapping mesh and VOF technology. The influence of a cross sea on ship motion performance under different wave direction angles, different wave heights and for different periods is analyzed. In addition, a method is also established for studying the ship's motion response based on potential flow theory, and it is found that ships sailing under superimposed waves will exhibit the phenomenon of beat vibration. Finally, by comparing the results obtained by the two methods, the consistency of the two methods is verified, which provides a strong basis for the safety assessment of ships in cross seas.